Determinants of the Net Interest Margins in BH Banks - Plakalović, Novo; Alihodzic, Almir A. (Industrija, 2015)
In this paper, the subject of analysis is influence of certain macroeconomic and microeconomic variables on bank net interest margins in Bosnia and Herzegovina (BH) for the period from 2008 to 2013 through a multiple linear regression models. The level and dynamics of NIM indicate the efficiency of financial intermediation. The observed period is characterized by the reduction in net interest margins of banks over the previous decade, which was characterized by high GDP growth, bank loans and high-interest rates and high profitability. Therefore, this study examines the factors that affect the level of net interest margins in the domestic banking industry. The main objective of this paper is to determine whether there is interdependence in the movement between the independent and dependent variables through a multiple linear regression. The net interest margin will be observed as a dependent variable, and liquidity risk, operating costs, credit risk, the index of market concentration, funding risk, the growth rate of gross domestic product and consumer price index will be used as independent variables.